Presentation of Spanish cattle, especially native breeds, and results of the research works dealing with them - Tőzsér, János; Vertséné Zándoki, Rita; Kosztolányiné Szentléleki, Andrea (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
This study presents the characteristics of 12 native Spanish cattle, and cattle to be preserved. The Authors introduce to the origin, distribution, colour, body weight and height of each breed. The classification of breeds according to FAO is described, and the utilisation of presented breeds nowadays is also emphasised. In the second part of the study, results of the research works dealing with Spanish cattle breeds to be protected are revealed in the fields of genetics, nutrition, meat production and meat quality.